2017
DOI: 10.1021/jacs.6b11072
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Volcano Trend in Oxygen Reduction Activity of Pt and Non-Pt Catalysts: In Situ Identification of the Site-Blocking Effect

Abstract: Proper understanding of the major limitations of current catalysts for oxygen reduction reaction (ORR) is essential for further advancement. Herein by studying representative Pt and non-Pt ORR catalysts with a wide range of redox potential (E) via combined electrochemical, theoretical, and in situ spectroscopic methods, we demonstrate that the role of the site-blocking effect in limiting the ORR varies drastically depending on the E of active sites; and the intrinsic activity of active sites with low E have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
99
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 32 publications
9
99
0
Order By: Relevance
“…For the other, some analytical and characterization techniques including Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray absorption/diffraction, Mössbauer spectroscopy and so on, allow us to monitor the ORR/OER in situ and confirm the actual active phase/intermediates and electrochemical behavior during ORR/OER on the surface of the materials. [17][18][19][20][21][22][23][24][25] This review describes recent progress on the design and synthesis of heterogeneous catalysts and their emerging catalytic activities in bifunctional ORR/OER used in alkaline electrolyte. The fundamentals of bifunctional ORR/OER electrocatalysis including reaction mechanism are first introduced.…”
mentioning
confidence: 99%
“…For the other, some analytical and characterization techniques including Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray absorption/diffraction, Mössbauer spectroscopy and so on, allow us to monitor the ORR/OER in situ and confirm the actual active phase/intermediates and electrochemical behavior during ORR/OER on the surface of the materials. [17][18][19][20][21][22][23][24][25] This review describes recent progress on the design and synthesis of heterogeneous catalysts and their emerging catalytic activities in bifunctional ORR/OER used in alkaline electrolyte. The fundamentals of bifunctional ORR/OER electrocatalysis including reaction mechanism are first introduced.…”
mentioning
confidence: 99%
“…As it has been demonstrated in the literature,,, the redox potential of the MN 4 catalyst could provide the information about the reactivity and the peroxide generation of the catalyst. It could be concluded that the onset potential is close to redox potential of metal center for the catalysts (e. g. FePc and FePc‐PcFe) promoting the 4‐electron transfer of ORR.…”
Section: Resultsmentioning
confidence: 98%
“…Transition metal macrocyclic compounds as ORR catalysts has gained interest in recent years for the ability to accurately characterize the catalytically active site and tunable reactivity. The ORR kinetics of these metal complexes has been studied extensively . Especially, transition metal like iron and cobalt phthalocyanines (MPcs) have been acknowledged as the typical catalysts for facilitating the ORR .…”
Section: Introductionmentioning
confidence: 99%
“…As one type of a high energy‐conversion device, proton‐exchange membrane fuel cells have received extensive concern all over the world owing to the serious energy crisis. Catalysts for the cathode reaction, the oxygen reduction reaction (ORR), are the key components of proton‐exchange membrane fuel cells that can directly affect the cell output performance . Platinum (Pt) serves as an efficient catalyst for the ORR because of its high activity and stability .…”
Section: Figurementioning
confidence: 99%